Discordant Supramolecular Fibres Reversibly Depolymerised by Temperature and Light. Issue 5 (23rd December 2020) - Gerth, Marieke; Berrocal, José Augusto; Bochicchio, Davide; Pavan, Giovanni M.; Voets, Ilja K.
Abstract: Synthetic stimuli responsive supramolecular polymers attract increasing interest for their ability to mimic the unique properties of natural assemblies. Here we focus on the well‐studied benzene‐1, 3, 5‐tricarboxamide (BTA) motif, and substitute it with two ( S )‐3, 7‐dimethyloctyl groups and an azobenzene photoswitch. We demonstrate the UV ( λ =365 nm) induced depolymerisation of the helical hydrogen‐bonded polymers in methylcyclohexane (MCH) through circular dichroism and UV‐vis spectroscopy in dilute solution (15 μm ), and NMR and iPAINT super‐resolution microscopy in concentrated solution (300 μm ). The superstructure can be regenerated after thermal depolymerization, whilst repeated depolymerisation can be reversed without degradation by irradiating at λ =455 nm. Molecular dynamics simulations show that the most energetically favourable configuration for these polymers in MCH is a left‐handed helical network of hydrogen‐bonds between the BTA cores surrounded by two right‐handed helices of azobenzenes. The responsiveness to two orthogonal triggers across a broad concentration range holds promise for use in, for example, photo‐responsive gelation. Abstract : The synthesis and characterisation of a chiral supramolecular motif are reported. The BTA motif self‐assembles into helical structures, wherein the hydrogen‐bonded core is of opposite helicity from the surrounding double helix formed by azobenzenes. This discordant structure is confirmed the most favoured conformation by MD simulations. The supramolecular fibres can be reversibly (de)polymerised by thermal cues and light irradiation.